Data_cod_flounder - Orio, Alessandro; Bergström, Ulf; Florin, Ann-Britt; Lehmann, Andreas; Šics, Ivo; Casini, Michele (Dryad Digital Repository, 2019)
Adult cod, juvenile cod and flounder CPUE data (in grams). The datasets contain also the associated bottom temperature, salinity and oxygen concentration of each haul as well as the latitude and longitude in decimal degrees.